2021
DOI: 10.1002/acs.3236
|View full text |Cite
|
Sign up to set email alerts
|

Linear‐like properties arise naturally in the adaptive control setting

Abstract: Summary Classical discrete‐time adaptive controllers typically provide asymptotic stabilization and tracking; usually the affect of the noise is at best bounded‐input bounded‐output. Recently we have shown that if you design a discrete‐time adaptive controller in just the right way, then in a variety of situations you not only obtain exponential stability, but also a bounded gain on the noise in every p−norm, as well as a never‐before‐seen linear‐like convolution bound on the input–output behavior. Quite surpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
(117 reference statements)
1
6
0
Order By: Relevance
“…We observe here that the controller (29a,b) and ( 30) fits into the paradigm of Section 2 with z ← ∅. In Reference 29 it is proven that (29a,b) and (30) provides exponential stability and a convolution bound for (23); by Theorems 1 and 2 we immediately see that the same is true in the presence of time-variation and/or unmodelled dynamics.…”
Section: Model Reference Adaptive Controlsupporting
confidence: 58%
“…We observe here that the controller (29a,b) and ( 30) fits into the paradigm of Section 2 with z ← ∅. In Reference 29 it is proven that (29a,b) and (30) provides exponential stability and a convolution bound for (23); by Theorems 1 and 2 we immediately see that the same is true in the presence of time-variation and/or unmodelled dynamics.…”
Section: Model Reference Adaptive Controlsupporting
confidence: 58%
“…The objective of this thesis is to design an adaptive controller which provides the same linear-like property of [35,36,38], while relaxing some of the assumptions; namely, we remove the need to know the plant delay and the sign of the high frequency gain. To achieve this, we apply Supervisory Control in discrete-time to both the classical d-stepahead adaptive tracking problem (this is, in itself, new) and to the step tracking problem using an integral pole placement controller.…”
Section: Objectivementioning
confidence: 99%
“…Observe that this estimator is the same as the weighted least-squares estimator, with two exceptions. Firstly, the true parameters θ * and estimated parameters θ are confined to a known set S in much the same way as in the Projection Algorithm setup used in [36,38] and other successful adaptive controllers. Secondly, instead of allowing the estimator to change its estimate at every time-step, it is required to 'pause' for the duration of the dwell time.…”
Section: Supervisory Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The impetus for this research is recent work by the second author in References 18–23, wherein it is shown that highly desirable linear‐like input–output behavior can be achieved in a particular adaptive control setting via a carefully designed recursive parameter estimation algorithm. This is expressed as a convolution bound, which confers exponential stability and a bounded gain on the noise in every p$$ p $$‐norm; such convolutions bounds are, as far as the authors are aware, a first in adaptive control and it allows one to use a modular approach* to prove robustness to a degree of unmodeled dynamics and tolerance to slow time‐varying parameters, 24,25 which is a highly desirable feature.…”
Section: Introductionmentioning
confidence: 99%